EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMPN SATU ATAP 2 JATIAGUNG KABUPATEN LAMPUNG SELATAN - Nasratul Elmi Arahab (UNISAN JURNAL, 2024)
Assessment becomes a very important part of teaching and learning. If learning has an important role to support the development of religious students, the evaluation function as providers of information to assess the success of the learning process is running. Without the presence of the evaluation activities, may not be able to find information about the advantages and disadvantages of teaching and learning activities that have been implemented. In practical terms, attitudes and actions also could not be taken. This study aims to determine: (1) Planning evaluation of learning subjects of Islamic education class nine student at SMPN Satu Atap 2 Jatiagung Kabupaten Lampung Selatan ; (2) Implementation of the learning evaluation subjects Islamic education in class nine in SMPN Satu Atap 2 Jatiagung Kabupaten Lampung Selatan ; (3) the results of the evaluation and feedback Islamic education learning class nine student at SMPN Satu Atap 2 Jatiagung Kabupaten Lampung Selatan as the basis for taking further action. This study is a qualitative research. The collected data were then analyzed using an inductive method of thinking. To analyze the data using qualitative descriptive analysis method. The process of collecting data the researcher uses several methods: observation, documentation and interview method. The results showed that, the planning phase has been formulated with a mature evaluation. This can be seen in teacher learning programs, both in the program and on the half of the lesson plan in detail time planning the evaluation, the evaluation division based on objective and scope, as well as the methods, techniques and types of evaluation that will be used. While the results showed that the implementation consists of the evaluation process and results showed that the really executed well, it can be seen from the teaching and learning activities where the teacher implemented the evaluation at each meeting. And to the results of the evaluation have shown that over 65% minimum standards and feedback to the students shown by the remedial program on material that has not been completed.